Predicting mechanical properties of 316L stainless steel subjected to SMAT: A sequential DEM-FEM investigation. (1st March 2021) - Zhang, Yongmei; Proust, Gwénaëlle; Retraint, Delphine; Wang, Huamiao; Gan, Yixiang
Highlights: A new DEM-FEM framework is introduced for predicting SMAT with rough surface sonotrode. DEM-generated spatial and statistic distributions of impact velocity, angle and position are used as input in FEM models. The impact angle distribution during SMAT affects the resulting plastic deformation, residual stress and surface roughness of target. Effects of treatment duration (impact density) on the evolution of SMAT treatment is demonstrated. Abstract: Surface mechanical attrition treatment (SMAT) is a specialized cold working method that is used to induce compressive residual stresses and to refine crystalline grains at the surface of metal components. This technique is increasingly employed in different industries, and the control and optimization of the method require a fundamental understanding and an accurate process modelling. In this study, a numerical modelling approach capable of accurately predicting the residual stress and plastic deformation during SMAT was developed by combining discrete element method (DEM) and finite element method (FEM). In the proposed framework, the spatial and statistic distributions of impact positions, angles and velocities from DEM simulations are utilized in the FEM simulations. The effects of treatment duration, shot number, shot size and impact angle distribution on residual stresses, plastic deformation and roughness of the treated component are investigated. The numerical results are compared with available experimental data with good agreements. The proposed numerical method demonstrates capabilities to establish the linkages between processing parameters and material properties during SMAT treatment. Graphical abstract: Image, graphical abstract